Inverses of measures on a class of discrete groups - C. Karanikas (International Journal of Mathematics and Mathematical Sciences)
We examine a class of groups G, having a certain growth condition. We given an estimate for the norm of the inverse of an element in ll(G) in terms of the spectral radius and the cardinality of the support.